Specialized pro-resolving mediators in neutrophil apoptosis regulation: unlocking novel therapeutic potential in kidney diseases - Kang, Yi; Jin, Qian; Zhou, Mengqi; Zheng, Huijuan; Li, Danwen; Wang, Xuezhe; Zhou, Jingwei; Wang, Yaoxian; Lv, Jie (Frontiers in Immunology, 2025)
Kidney diseases represent a diverse group of disorders with pathogenic mechanisms involving multiple pathological processes, including inflammation, immunity, and cell death. Neutrophils, as primary effector cells in inflammatory immune responses, participate in defending against renal infection and injury by releasing reactive oxygen species, proteases, and cytokines. However, persistent neutrophil activation is considered a crucial driver of kidney disease progression. Neutrophil apoptosis represents a critical turning point between inflammatory progression and resolution. Specialized pro-resolving mediators (SPMs) are endogenous anti-inflammatory mediators that play a critical role in resolving inflammation. They not only induce neutrophil programmed cell death and promote macrophage-mediated efferocytosis of apoptotic cells but also inhibit neutrophil infiltration and degranulation, ultimately facilitating the restoration of inflammatory microenvironment and tissue homeostasis. This review concentrates on elucidating the mechanisms by which SPMs regulate neutrophil apoptosis and systematically demonstrates their potential as novel therapeutic targets in kidney diseases.